Mentoring of Mekarsaluyu Women Farmers Group as MSMEs Producers of One Village One Product in Utilizing Digital Marketing as a Promotional Media - Wardhana, Adhitya Ikhsani; Silaningsih, Endang; Suryani, Danu; Yuningsih, Erni; Maulana, Lucky Hikmat (Jurma : Jurnal Program Mahasiswa Kreatif, 2024)
BARAYU MSMEs is an OVOP producer of MSMEs in Margaluyu Village that needs help increasing its income due to the marketing methods used. For this reason, business actors need changes in the promotion model to maintain their business. Technological developments have made social media widely used, opening up opportunities for business actors as a medium for product promotion. This service aims to provide knowledge and promote products, assist in creating trademarks, MSMEs logos, websites, and skills for MSMEs in designing product promotions on social media and increasing product sales. Assistance uses the Participatory Action Research (PAR) method: observation, interviews, discussions, assistance, and Output. The results obtained after carrying out this service are increased knowledge and Understanding of BARAYU MSMEs owners regarding the existence and potential of social media in promoting products, the creation of the brand name "BARAYU," the creation of a logo and website as well as MSMEs social media accounts, increased skills of MSMEs owners in using social media as a promotional medium, and increasing the number of product sales.